Android-Based Digital Media through Green Marketing in the Lake Toba Area on English Language Skills - Idawati Situmorang; Muhammad Sakban (ITScience (Information Technology and Science), 2025)
The low level of public awareness, especially in small towns, about the importance of equipping ourselves with foreign language skills. Students are still often afraid to make mistakes when using English. Digital media offers various advantages that can increase the effectiveness of English learning, one of which is the Android smartphone, which can be used as an alternative medium to obtain learning about various English language skills. Students can use it as an English learning tool. Improving English skills through green marketing is an effort to train English communicatively through marketing Lake Toba tourism using English so that students interact directly with foreign tourists and help to promote Lake Toba globally. Collaborative classroom action research with the Kemmis & McTaggart model. The subjects of the study were 23 students of AMIK Parbina Nusantara. The instruments used in the observation were assessment sheets and documentation. The indicator of success in this study is when the average English speaking ability has reached 80%. The results of this study indicate an increase in English speaking skills. This is evidenced by an increase in the average English speaking skills of students in the Pre-action of 60.04%, increasing to 78.08% in the Cycle I action, and reaching 90.51% in the Cycle II action. The English speaking skills of students increased after researchers provided action through android-based digital media through green marketing in the Lake Toba tourist area.